Molecular biology of the cell - Alberts, Bruce; Heald, Rebecca, 1963-; Johnson, Alexander (Alexander D.); Morgan, David Owen, 1958-; Raff, Martin C.; Roberts, K. (Keith); Walter, Peter (Professor) (New York, NY : W. W. Norton & Company, 2022)
'As the amount of information in biology expands dramatically, it becomes increasingly important for textbooks to distill this vast amount of scientific knowledge into concise principles and enduring concepts.'Molecular Biology of the Cell', Seventh Edition accomplishes this goal with clear writing and beautiful illustrations. The Seventh Edition has been extensively revised and updated with the latest research in cell biology, and it provides an exceptional framework for teaching and learning.'Molecular Biology of the Cell' is widely used in introductory courses at the university level, being considered as a reference in many libraries and laboratories around the world. It describes the current understanding of cell biology and includes basic biochemistry, experimental methods for investigating cells, the properties common to most eukaryotic cells, the expression and transmission of genetic information, the internal organization of cells, and the behavior of cells in multicellular organisms.'Molecular Biology of the Cell' has been described as'the most influential cell biology textbook of its time''--
Part I. Introduction to the Cell -- Chapter 1. Cells, genomes, and the diversity of life -- Chapter 2. Cell chemistry and bioenergetics -- Chapter 3. Proteins -- Part II. Basic Genetic Mechanisms -- Chapter 4. DNA, chromosomes, and genomes -- Chapter 5. DNA replication, repair, and recombination -- Chapter 6. How cells read the genome : From DNA to protein -- Chapter 7. Control of gene expression -- Part III. Ways of Working with Cells -- Chapter 8. Analyzing cells, molecules, and systems -- Chapter 9. Visualizing cells and their molecules -- Part IV. Internal Organization of the Cell -- Chapter 10. Membrane structure -- Chapter 11. Small-molecule transport and electrical properties of membranes -- Chapter 12. Intracellular organization and protein sorting -- Chapter 13. Intracellular membrane traffic -- Chapter 14. Energy conversion and metabolic compartmentation : Mitochondria and chloroplasts -- Chapter 15. Cell signaling -- Chapter 16. The cytoskeleton -- Chapter 17. The cell cycle -- Chapter 18. Cell death -- Part V. Cells in Their Social Context -- Chapter 19. Cell junctions and the extracellular matrix -- Chapter 20. Cancer -- Chapter 21. Development of multicellular organisms -- Chapter 22. Stem cells in tissue homeostasis and regeneration -- Chapter 23. Pathogens and infection -- Chapter 24. The innate and adaptive immune systems -- Glossary -- Index.
Glossary = pages G-1 through G-37. Index = pages I-1 through I-70.
Includes bibliographical references and index.
Keywords: Cells; Molecular biology